MENTORING NEW NURSES IN STRESSFUL TIMES - Young, Lisa (Operating Room Nurses Association of Canada Journal, 2009)
Meeting benchmarks of Ontario’s Wait Time Strategy and the expansion of The Ottawa Hospital are key issues driving the recruitment of perioperative nurses in Ottawa and Eastern Ontario. Added pressures resulting from Canada’s aging population and a nationwide nursing shortage mean perioperative nurses are overworked and understaffed. Preceptoring new members of staff raises valid concerns as many of the new recruits have little or no operating room experience. The Dreyfus Model of Skill Acquisition demonstrates the importance of time and patience in supporting the learning process. Mentoring is a valuable strategy in an effort to teach and guide new nurses, to increase nursing retention, and to promote professional growth and recognition. Building successful mentorship programs, through the creation of healthy organizational cultures, transformational leadership and staff development programs, will strengthen support for nurses in stressful times. The stress of meeting the province-wide benchmarks outlined in Ontario’s Wait Time Strategy and the expansion of perioperative services at The Ottawa Hospital in Ontario are two key issues driving the need for the recruitment of nurses into the specialty of perioperative nursing. As a result of Canada’s aging population and a nationwide nursing shortage, perioperative nurses are over-worked and under-staffed while being faced with the pressure to preceptor new staff members while struggling to meet the daily demands of the wait list strategy. This article discusses current trends in healthcare and the career path changes being made by many nurses in response to the demand for specialty trained nurses. It is followed by a brief explanation of the Dreyfus Model of Skill Acquisition. Mentoring is presented as an effective strategy in the guidance and teaching of new nurses with a discussion of the benefits and suggestions on how to build a successful mentorship program to support nurses in these stressful times.